A COMPARISON OF MACERATION AND SOCKLETATION EXTRACTION METHODS ON FLAVONOID CONTENTS OF BELUNTAS LEAF EXTRACT - Handik Hendratama; Diana Novita Sari; Alifatun Nada; Aulia Firda Alfiana (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
This research aims to analyze the flavonoid compound of beluntas leaves (Pluchea indica L) using maceration and soxhletation extraction methods. Extraction uses 96% methanol solvent with a ratio of 1:10, 1:15, 1:20 w/v and with a soxhletation extraction time of 60 minutes, 120 minutes, 180 minutes at a temperature of 80oC, while the maceration time is 3 days at room temperature. Qualitative testing of flavonoid compounds uses the Shinoda test which is characterized by a change in the color of the sample to yellow or red-orange. The test results of all samples used showed the presence of flavonoid compounds which were characterized by changes in the color of the samples from yellow to red-orange. The research results showed that the best flavonoid content using the maceration extraction method was 51.52 mg QE/g at a ratio of 1:20 w/v, while the flavonoid content using the soxhletation extraction method was 53.96 mg QE/g at a ratio of 1:20 w/v.